Exploring the Formation of Exercise Habits with the Latent Growth Model. Issue 5 (October 2019) - Lee, Yoongu; Yoon, Yong-Jin
This study investigated the antecedent factors affecting exercise preparation and performance habits and provides basic data for the development of health promotion interventions, based on what was found to be most effective in improving intention and habit. The participants were 114 university students who were willing to participate regularly in exercise and physical activities and interested in forming exercise habits. After coding, we analyzed the complete data set through frequency analysis, reliability, and latent growth model analysis. The provision of early rewards positively affected an initial exercise preparation habit. Both initial consistency and development of consistency also positively affected the development of exercise preparation, and initial behavioral complexity positively affected initial exercise preparation. However, no factors influenced an exercise performance habit. Thus, forming an exercise preparation habit requires fun, personal control, and repetitive behavior while forming an exercise performance habit is particularly challenging. These results may help construct a program for continuous exercise participation.